Dignity realization of patients with stroke in hospital care: A grounded theory - Rannikko Sunna; Stolt Minna; Suhonen Riitta; Leino-Kilpi Helena (My University, 2022)
Background:
Dignity is seen as an important but complex concept in the healthcare context. In this context, the discussion of dignity includes concepts of other ethical principles such as autonomy and privacy. Patients consider dignity to cover individuality, patient’s feelings, communication, and the behavior of healthcare personnel. However, there is a lack of knowledge concerning the realization of patients’ dignity in hospital care and the focus of the study is therefore on the realization of dignity of the vulnerable group of patients with stroke.
Aim:
The aim of the study was to create a theoretical construct to describe the dignity realization of patients with stroke in hospital care.
Research design and participants:
Patients with stroke (n = 16) were interviewed in 2015 using a semi-structured interview containing open questions concerning dignity. The data were analyzed using constant comparison of Grounded Theory.
Ethical considerations:
Ethical approval for the research was obtained from the Ethics Committee of the University. The permission for the research was given by the hospital. Informed consent was obtained from participants.
Findings:
The “Theory of Dignity Realization of Patients with Stroke in Hospital Care” consists of a core category including generic elements of the new situation and dignity realization types. The core category was identified as “Dignity in a new situation” and the generic elements as health history, life history, individuality and stroke. Dignity of patients with stroke is realized through specific types of realization: person-related dignity type, control-related dignity type, independence-related dignity type, social-related dignity type, and care-related dignity type.
Discussion:
The theory has similar elements with the previous literature but the whole construct is new. The theory reveals possible special characteristics in dignity realization of patients with stroke.
Conclusion:
For healthcare personnel, the theory provides a frame for a better understanding and recognition of how dignity of patients with stroke is realized.